2017
DOI: 10.1186/s13098-017-0246-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of type 1 diabetes mellitus in children and adolescents: a case–control study

Abstract: BackgroundType 1 diabetes mellitus (T1DM) is one of the most common pediatric diseases and its incidence is rising in many countries. Recently, it has been shown that metabolites other than glucose play an important role in insulin deficiency and the development of diabetes. The aim of our study was to look for discriminating variation in the concentrations of small-molecule metabolites in the plasma of T1DM children as compared to non-diabetic matched controls using proton nuclear magnetic resonance (1H-NMR)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…L‐serine concentration has in several studies been found to be significantly altered in diabetes. A study of children with type 1 diabetes and non‐diabetic controls found that the concentration of L‐serine in plasma was decreased by 42% in patients . Similar studies of patients with type 2 diabetes have found reduced L‐serine concentration in blood .…”
mentioning
confidence: 84%
“…L‐serine concentration has in several studies been found to be significantly altered in diabetes. A study of children with type 1 diabetes and non‐diabetic controls found that the concentration of L‐serine in plasma was decreased by 42% in patients . Similar studies of patients with type 2 diabetes have found reduced L‐serine concentration in blood .…”
mentioning
confidence: 84%
“…Previous studies on the lipid profile analysis of patients with DM concerned mainly type 2 DM, where the importance of abnormalities in the lipid profile in the aetiopathogenesis of cardiovascular diseases has been confirmed [23]. Published studies on lipid profile assessments in patients with T1DM in relation to a control group without diabetes showed significantly lower levels of analysed parameters in patients with T1DM [24]. New data are expected soon from the completed Adolescent type 1 Diabetes cardio-renal Intervention Trial (AdDIT) to provide information about potential renal and cardiovascular protective effects of ACEI and statins in high-risk adolescents [25].…”
Section: Original Papermentioning
confidence: 94%
“…The correlation coefficient gives a linear indication of the strength of the correlation and is independent of the intensity of the variable so it is a better measure for the reliability of the variable in the classification process. Strongly discriminating variables have a clear covariance with a high absolute value for the correlation coefficient [ 43 ]. The quality of the model was evaluated by the R 2 and Q 2 values, defining the variance explained (indicating goodness of fit) and the variance predicted by the model, respectively.…”
Section: Methodsmentioning
confidence: 99%